DNA hypomethylation traits define human regulatory T cells in cutaneous tissue and identify their blood recirculating counterparts - Beumer, Niklas; Imbusch, Charles; Kaufmann, Tamara; Schmidleithner, Lisa; Gütter, Kathrin; Stüve, Philipp; Marchel, Harriet; Weichenhan, Dieter; Bähr, Marion; Ruhland, Brigitte; Marini, Federico; Sanderink, Lieke; et al. (Nature immunology, 2025)
CD4+ regulatory T (Treg) cells in tissues play crucial immunoregulatory and regenerative roles. Despite their importance, the epigenetics and differentiation of human tissue Treg cells are incompletely understood. Here, we performed genome-wide DNA methylation analysis of human Treg cells from skin and blood and integrated these data into a multiomic framework, including chromatin accessibility and gene expression. This analysis identified programs that governed the tissue adaptation of skin Treg cells. We found that subfamilies of transposable elements represented a major constituent of the hypomethylated landscape in tissue Treg cells. Based on T cell antigen receptor sequence and DNA hypomethylation homologies, our data indicate that blood CCR8+ Treg cells contain recirculating human skin Treg cells. Conversely, differences in chromatin accessibility and gene expression suggest a certain reversal of the tissue adaptation program during recirculation. Our findings provide insights into the biology of human tissue Treg cells, which may help harness these cells for therapeutic purposes.